The Microemulsion Stability of Virgin Coconut Oil Based on Tradition of Melala Sumbawa's Society - Devi Ayu Septiani; Jono Irawan; Hermansyah Hermansyah; Yayuk Andayani (The University of Mataram, 2021)
The Melala is a tradition of the Sumbawa people who use coconut milk to obtain Sumbawa oil for traditional medicine. Coconut milk is a colloidal system of stable oil in water (O/W) microemulsion. Within a particular time, the emulsion will split to produce oil (VCO), protein, and water due to the colloid equilibrium on the stability of the coconut milk emulsion. The purpose of this study was to compare the microemulsion stability of the coconut milk colloid system. The VCO was isolated by heating, enzymatically, acidifying, and adding whiting methods for comparison. The physical stability of the O/W microemulsion was measured by the volume of VCO produced from various isolation methods in simple laboratory experiments. The results showed that the physical stability of the O/W microemulsion on VCO isolation by enzymatic method using papain enzyme was the least.